2019
DOI: 10.1371/journal.pone.0216998
|View full text |Cite
|
Sign up to set email alerts
|

Development of an easy and cost-effective method for non-invasive genotyping of insects

Abstract: Non-invasive genotyping methods provide valuable information on insect populations. However, poor DNA amplification and time-consuming sampling procedures limit these methods, especially for small insects. An efficient and convenient method was developed for non-invasive, non-lethal genotyping of a large insect, Mythimna separata , and a small insect, Drosophila melanogaster , by amplification of endogenous and exogenous, nuclear and mitochondrial genes from insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Finally, some mitochondrial loci might be more challenging to amplify from frass than others. Similar to another publication [40], we were unsuccessful in amplifying COI in our beetle frass samples, although these primers successfully amplified a subset of museum specimens (S3 Table).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Finally, some mitochondrial loci might be more challenging to amplify from frass than others. Similar to another publication [40], we were unsuccessful in amplifying COI in our beetle frass samples, although these primers successfully amplified a subset of museum specimens (S3 Table).…”
Section: Discussionsupporting
confidence: 71%
“…Frass has also been utilized for molecular species identification, which can be indispensable in distinguishing closely related species [30]. In addition, frass genetic methods can reveal gender and identify transgenic individuals, even in visually similar early larval stage insects [40]. A PCR-based approach has been documented for invasive wood-boring insects [41] but there is also potential for non-lethal genetic sampling of rare and protected organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the success of the non-destructive approach is not guaranteed on all occasions and purposes. Obtaining useful genetic information from samples, collected in a non-destructive way, seem to have a wide range of success rate among different insect taxa and for different purposes [ 14 , 15 , 17 , 21 , 48 ]. These results hint that any non-destructive approach should not be considered universal but rather decided upon after preliminary screening.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the use of residual egg debris has advantages over other documented noninvasive genetic sampling methods involving larval exuviae, frass, or the more traditional removal of tissue samples (e.g., palps, wing clippings, legs) from adult organisms. These can be problematic logistically as they often require longer organism holding times, necessitate organism removal from the environment, or may result in a limited number of viable available samples [18,19,20,21,22]. For example, Saarinen et al [13] demonstrated that wing clips represent a viable, non-lethal method of obtaining DNA from a federally endangered butterfly.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being nonlethal, such methods still require capture and handling of the target organism which can inflict significant stress, inadvertent damage, or death, and may not be feasible for low density or at-risk populations. Alternatively, researchers have also successfully secured DNA from frass, exuviae, and hemolymph in defensive secretions [18,19,20,21,22]. However, these sources may not be broadly available for many taxa and certainly offer significant challenges for reliable collection in the field.…”
Section: Introductionmentioning
confidence: 99%